A survey in infections caused by Mycoplasma sinoviae and Mycoplasma galisepticum in broiler chickens slaughtered in General Pico using the slide quick agglutination technique (Veterinary Science, 2017)
A survey on broiler chickens that were allotted to slaughtering in the city of General Pico to know the antibodies sero prevalence against Mycoplasma gallisepticum and Mycoplasma sinoviae. 400 samples were taken. The samples underwent the Slide Quick Agglutination technique (ARP) with commercial antigen for the two pathogen agents, resulting 5 fowls (1.25%) positive to Mycoplasma gallisepticum and 3 birds (0.75%) positive to Mycoplasma sinoviae. Considering these outcomes the conclusion is that mycoplasmosis is not a considerable pathology in the city at present, such as it actually is in other regions of the country
Keywords: Mycoplasmosis; Mycoplasma gallisepticum; Mycoplasma sinoviae